Discontinuous vs. continuous drinking of ethanol in peripubertal rats : effect on 24-hour pattern of hypophyseal-gonadal axis activity and anterior pituitary oxidative stress - Fernández Mateos, María P. (2012)
Fil: Fernández Mateos, María P. Universidad Complutense. Facultad de Medicina. Departamento de Bioquímica y Biología Molecular; España